Percutaneous compression plate versus proximal femoral nail anti-rotation in treating elderly patients with intertrochanteric fractures: a prospective randomized study - Guo, Qingshan; Shen, Yue; Zong, Zhaowen; Zhao, Yufeng; Liu, Huayu; Hua, Xiang; Chen, Hui (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2013)
The treatment and management of hip fracture poses a great challenge for clinicians in osteology and surgery. The aim of this study is to compare the clinical effectiveness of the percutaneous compression plate (PCCP) versus proximal femoral nail anti-rotation (PFNA) in the treatment of intertrochanteric fractures in elderly patients. A prospective randomized study was carried out from January 2008 to October 2011 involving 90 elderly patients with intertrochanteric fractures (90 hips) who underwent minimally invasive surgery using the PCCP or PFNA. Evaluation variables, including operation time, intra- and perioperative blood loss, duration of hospital stay, incidence of postoperative complications, and final clinical outcomes by the end of follow-up, were used to compare the benefits of these two implants. Among 90 subjects, 45 received PCCPs and 45 received PFNAs. The baseline characteristics of the two groups were comparable. The median follow-up time was 16.9months (12–24months). In the PCCP group, the mean operative time was 53min (40–75min), and the mean intra- and perioperative blood losses were 100.7ml (60–150ml) and 916ml (433–1339ml), respectively, which were significantly lower than those in the PFNA group. Nevertheless, there was no statistical difference in the incidence of postoperative complications and final clinical outcomes including pain complaints, range of motion of the hip, postoperative hip function at 12months, and the recovery of walking ability to pre-injury status between these two implants. Overall, the PCCP and PFNA appear to have similar clinical effects in treating elderly patients with intertrochanteric fractures, although the PCCP provided shorter operation times and less blood loss than PFNA. Both implants discussed were demonstrated to be ideal for the treatment of femoral intertrochanteric fractures in elderly patients.